Advances in organic microporous membranes for CO2 separation. Issue 1 (6th December 2022) - Wang, Yuhan; Jiang, Haifei; Guo, Zheyuan; Ma, Hanze; Wang, Shaoyu; Wang, Hongjian; Song, Shuqing; Zhang, Junfeng; Yin, Yan; Wu, Hong; Jiang, Zhongyi; Guiver, Michael D.
Abstract : This Perspective focuses on innovation and advanced design of membranes for carbon dioxide separation, triggered by new organic microporous materials. Abstract : Carbon emission has become a worldwide concern with global warming and concurrent climate changes. Carbon capture using membrane-based technology offers an effective way to achieve controllable carbon emission and carbon neutrality. During the past decade, organic microporous materials have demonstrated superior physical and chemical properties and triggered a revolution in novel membrane structures. In this Perspective, we focus on progress in advanced organic microporous membranes, with an emphasis on highlighting confined mass transport mechanisms, design principles and representative organic microporous membranes as well as their CO2 separation applications. First, we discuss the abnormal confinement effect in organic microporous membrane channels based on a physical/chemical confined mechanism to understand CO2 molecular transport behavior. Second, we propose three design principles, nano-assembly engineering, reticular engineering, and microenvironment engineering, to construct task-specific membrane structures. Third, we summarize four categories of organic microporous membrane materials, which are polymers of intrinsic microporosity (PIM), graphene oxide (GO), metal–organic framework (MOF) and covalent organic framework (COF). Last, we provide a perspective on the opportunities and major challenges to achieve the transformation from advanced membranes to real-world applications.